Developing effective national policy instruments to promote teaching excellence: evidence from the English case. Issue 1 (2nd January 2022) - Ashwin, Paul
ABSTRACT: There is increasing international focus on system-wide schemes of teaching excellence in higher education. In this article, I explore national policy instruments intended to promote and measure teaching excellence. There appears to be very limited knowledge about what underpins the effective design of policy instruments for teaching excellence. This article attempts to address this gap by examining the English case, which involved two distinct approaches to developing teaching excellence across the higher education system. The available evidence suggests that neither policy instrument was particularly successful in increasing teaching excellence across the sector. This highlights the challenges of developing effective teaching excellence policy instruments. Based on this analysis, recommendations are made for the more effective design of policy instruments aimed at teaching excellence in higher education.